2022
DOI: 10.3390/ijms23094808
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pharmacology of Inflammation Resolution in Atherosclerosis

Abstract: Atherosclerosis is one of the most important problems of modern medicine as it is the leading cause of hospitalizations, disability, and mortality. The key role in the development and progression of atherosclerosis is the imbalance between the activation of inflammation in the vascular wall and the mechanisms of its control. The resolution of inflammation is the most important physiological mechanism that is impaired in atherosclerosis. The resolution of inflammation has complex, not fully known mechanisms, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 318 publications
0
8
0
Order By: Relevance
“…117 An holistic approach to treat inflammatory vasculopathy and unresolved inflammation has been proposed in diseases other than SCD such as in cardiovascular disease or atherosclerosis by administrating ω-3 fatty acids (ω-3 PUFAs). [118][119][120] Previous studies in both mouse models and patients with SCD have shown beneficial effects of dietary supplementation with ω-3 PUFAs preparations. [121][122][123][124] As shown in Table 1, two clinical studies with omega(ω)-3 fatty acid supplementation are actively recruiting SCD patients.…”
Section: Agents Targeting the Hemolysis-vascular Endothelial Axismentioning
confidence: 99%
“…117 An holistic approach to treat inflammatory vasculopathy and unresolved inflammation has been proposed in diseases other than SCD such as in cardiovascular disease or atherosclerosis by administrating ω-3 fatty acids (ω-3 PUFAs). [118][119][120] Previous studies in both mouse models and patients with SCD have shown beneficial effects of dietary supplementation with ω-3 PUFAs preparations. [121][122][123][124] As shown in Table 1, two clinical studies with omega(ω)-3 fatty acid supplementation are actively recruiting SCD patients.…”
Section: Agents Targeting the Hemolysis-vascular Endothelial Axismentioning
confidence: 99%
“…These lipids activate immune cells that trigger a continuous secretion of pro-inflammatory factors and adhesive molecules (VCAM and ICAM). These latter provoke the sustained recruitment of immune cells in the endothelium and enhance the formation of atherosclerotic plaques [ 182 ]. In coronary artery diseases, diverse mechanisms, such as immune complex-mediated and cell-mediated inflammation, contribute to its growth [ 181 ].…”
Section: Designed Polyphenolic-loaded Nanocarriers For Inflammation-m...mentioning
confidence: 99%
“…Resolution of Inflammation (RoI) is not a passive process but indeed a dynamic phenomenon, finely tuned by several soluble mediators, including the so called Specialised Pro-resolving Mediators (SPMs), such as Lipoxins (LXs), Resolvins, Protectins, and Maresins ( Kotlyarov and Kotlyarova, 2022 ). Thanks to the ground-breaking work of Godson and collaborators, our group has been mainly focusing on elucidating the role of LXs in RoI and as a novel therapeutic target.…”
Section: Atherosclerosis: the ‘Silent Killer’ Of The 21st Centurymentioning
confidence: 99%
“…The ROS molecules present in the inflammatory milieu elicit in vivo and in vitro lipid peroxidation, wherein there is oxidative decomposition of omega-3 and -6 polyunsaturated fats of phospholipids for LX production. Research suggests that arachidonic acid is a vital LDL present as an endogenous phospholipid in biological membranes or through dietary supply of linoleic acid or animal protein ( Kotlyarov and Kotlyarova, 2022 ). With the resolution of inflammation being a driving factor in atherosclerosis prevalence and development, there is growing consensus into the potential role that synthetic lipoxin mimetics may possess as a future treatment for this disease.…”
Section: Novel Targets In the Resolution Of Atherosclerosismentioning
confidence: 99%